2008
DOI: 10.2478/v10046-008-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of Stress Response Performing Endotracheal Intubation By Direct Laryngoscopy, Fibreoptic Intubation And Intubation By The Glidescope Laryngoscope

Abstract: Comparison Of Stress Response Performing Endotracheal Intubation By Direct Laryngoscopy, Fibreoptic Intubation And Intubation By The Glidescope Laryngoscope Stress response is regulated by two primary neuroendocrine systems—the hypothalamuspituitary- adrenocortical (HPA) and sympathetic adrenomedullary (SAM) systems. Salivary alphaamylase (AA) levels can be used as an index of the SAM activity, and serum cortisol as an index of HPA activity. The aim of the study was to compare patient stress response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…1,2 Thus, in VL group pre and post-intubation change in level of salivary alpha amylase was insignificant (p=0.919), but it was highly significant(p=0.0001), in DL and FOB group, which shows that Video laryngoscopy causes least neuroendocrine stress response to intubation in comparison to Direct laryngoscopy and Fiberoptic group. Our result was well supported by Natalja et al (2008), 7 who studied comparison of stress response performing intubation by direct laryngoscopy, fiberoptic intubation and the glidescope video laryngoscope and concluded that shorter and more confident intubations with a glide scope produces less nociceptive stimulus and less stress to the patient. In VL patient the SAA level after intubation significantly decreased, but in ML and FOB patients significantly increased.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…1,2 Thus, in VL group pre and post-intubation change in level of salivary alpha amylase was insignificant (p=0.919), but it was highly significant(p=0.0001), in DL and FOB group, which shows that Video laryngoscopy causes least neuroendocrine stress response to intubation in comparison to Direct laryngoscopy and Fiberoptic group. Our result was well supported by Natalja et al (2008), 7 who studied comparison of stress response performing intubation by direct laryngoscopy, fiberoptic intubation and the glidescope video laryngoscope and concluded that shorter and more confident intubations with a glide scope produces less nociceptive stimulus and less stress to the patient. In VL patient the SAA level after intubation significantly decreased, but in ML and FOB patients significantly increased.…”
Section: Discussionsupporting
confidence: 87%
“…This shows that in stress response, both neuroendocrine systems (HPA and SAM) are of importance and can react differently. 3 Observing the above facts in our study it can be said that intubation with fiberoptic requires the longest time, causing the greatest pressor response 5,6 to the patients while, intubation with video laryngoscopy causes lesser stress response 4,7 to the patients. Thus, the video laryngoscope is a reliable technique for patient's safety.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations